PERLINDUNGAN HUKUM TERHADAP SYAHBANDAR DALAM PELAKSANAAN TUGASNYA SEBAGAI PENEGAK HUKUM MARITIM DI INDONESIA - Takdir, Takdir (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACT. Syahbandar has an important role in supervising ship and port operations, as well as ensuring compliance with applicable maritime regulations. However, in carrying out his duties as a maritime law enforcer, Syahbandar is often faced with various challenges. One of the main challenges is the lack of adequate legal protection in the performance of its duties. This research is about the legal protection that applies to Syahbandar in carrying out his duties as a maritime law enforcer in Indonesia, the obstacles and challenges faced by Syahbandar in the implementation of law enforcement duties in Indonesia's maritime territory. Using normative legal research, which is legal research conducted by researching literature materials. Syahbandar has clear authority in supervision and law enforcement in the port area, the lack of clarity in regulations related to legal protection makes them vulnerable to intimidation. These challenges include overlapping authority with other law enforcement agencies, limited resources and infrastructure, and threats or intimidation from interested parties. Improve coordination between Syahbandar and other law enforcement agencies such as Bakamla, the Water Police, and the Indonesian Navy, so as to create a clearer and more effective division of duties in maritime law enforcement and to draft or revise regulations governing the authority of Syahbandar, so that there is no overlap. Keywords: Legal Protection, Syahbandar, Law Enforcement.